"Free" and "unfree" money in German prisons: The role of accounting in educating public service users. (16th January 2020) - Iloga Balep, Nathalie; Junne, Jaromir
Abstract: This paper explores how public organizations use accounting as a pedagogical instrument for educating individual citizens. Drawing on conceptions of financial literacy and governmentality, our paper presents the findings of a qualitative case study of German prisons and analyzes how accounting practices shape interactions between public organizations and individual citizens. Our findings show how three types of financial accounts— prison money, gate money, and private money— grant prisoners differentiated access to funds. Prison administrators refer to these accounts as "free" or "unfree, " depending on whether prisoners can decide how the money will be used. The study reveals how German law, ministries, and prison administrations attach three basic virtues to prisoner accounts— legal consumption, financial prudence, and social responsibility —in an attempt to include individuals (back) into a population of economically and socially functioning citizens. To public management research, this paper contributes a description of how public institutions employ accounting as a pedagogical technology in interactions with individual citizens. To prior works on financial literacy, we add the idea that educative measures not only produce viable and disciplined market actors, but also transport specific virtues of being a social citizen. Finally, our study discusses how disciplinary and postdisciplinary notions of accounting interact and provide possibilities for governing through freedom—even behind bars.